Aktivisme Transnasional The Asian Peasant Coalition di Indonesia - Muh. Asy'ari (Journal of International and Local Studies, 2020)
This research is based on the existence of the transnational peasant movement and the interaction of the Indonesian local peasant movement in transnational agrarian politics. This research takes a case study of the Asian Peasant Coalition (APC) as a transnational farmer organization in Indonesia. Using qualitative methods carried out by reviewing documents and interviews, this study seeks to explain the transnational activism of the Asian Peasant Coalition (APC) within the collective identity and encourage the struggle of local peasant organization in Indonesia. To explain the above, this study uses the Transnational Activism concept developed by Sidney Tarrow to analyze and transnational activities. In addition, this study also uses framing theory in the collective to analyze how the solidarity of transnational farmer movements and local farmer movements can be formed and maintained during the advocacy process. This research finds and concludes that the ordering of local land grabbing collective problems campaigned and advocated at the global level by APC is carried out through the stages of development of Transnational Contention. The impact of this phase is what supports the problems of local farmers to become part of the national movement and will eventually create solidarity movements to support farmers at the local level. It is in this context that the solidarity and collective identity of the transnational peasant movement is formed and enables the birth of transnational actors at the local level.